2019
DOI: 10.3389/fneur.2019.00334
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of T1w/T2w Ratio Improves Detection of Tissue Damage in Multiple Sclerosis

Abstract: Normal appearing white matter (NAWM) damage develops early in multiple sclerosis (MS) and continues in the absence of new lesions. The ratio of T1w and T2w (T1w/T2w ratio), a measure of white matter integrity, has previously shown reduced intensity values in MS NAWM. We evaluate the validity of a standardized T1w/T2w ratio (sT1w/T2w ratio) in MS and whether this method is sensitive in detecting MS-related differences in NAWM. T1w and T2w scans were acquired at 3 Tesla in 47 patients with relapsing-remitting MS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 59 publications
(64 reference statements)
5
39
1
Order By: Relevance
“…It should be noted that there is controversy in the literature as to whether the ratio of T1w and T2w images (T1w/T2w ratio) in grey matter is a reliable estimate of cortical myelin content. Nevertheless, there is a growing consensus that the T1w/T2w ratio is a marker of general white-matter microstructure in both health and disease [33][34][35] provided that a correctly standardized measure of T1w/T2w is applied 36 . Our analysis uses the neuroimaging in the HCP dataset of healthy participants with isotropic spatial resolution of 0.7 mm, which enables highly accurate individual maps of cortical myelin content and thickness 18 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that there is controversy in the literature as to whether the ratio of T1w and T2w images (T1w/T2w ratio) in grey matter is a reliable estimate of cortical myelin content. Nevertheless, there is a growing consensus that the T1w/T2w ratio is a marker of general white-matter microstructure in both health and disease [33][34][35] provided that a correctly standardized measure of T1w/T2w is applied 36 . Our analysis uses the neuroimaging in the HCP dataset of healthy participants with isotropic spatial resolution of 0.7 mm, which enables highly accurate individual maps of cortical myelin content and thickness 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous non-conventional and advanced imaging modalities are currently under investigation that may help improve visualization and quantification of (covert) tissue damage in the gray and white matter of the brain and the spinal cord and could be used as an imaging surrogate of remyelination and repair; among them are magnetization transfer imaging, diffusion tensor imaging, myelin water imaging, susceptibility weighted imaging, magnetic resonance spectroscopy, sodium imaging, PET imaging, ultra-high field imaging at 7 Tesla, functional imaging with resting state fMRI, T1/T2-weighted ratio calculable from conventional T1-and T2-weighted images, machine-learning based imaging, magnetic resonance elastography, and several others, none of which will probably be used in clinical practice in the near future (27,52,83,88,(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135). Nonetheless, these endeavors are important to deepen our understanding of mechanisms of tissue damage in MS and to devise better imaging endpoints for clinical trials and routine care than those currently in use.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…This may suggest that MM can detect modest reductions in myelin within NAWM before a MS plaque is fully formed. Previous studies have also demonstrated the use of MMs to determine changes in the NAWM of MS patients ( Beer et al, 2016 , Cooper et al, 2019 ). While our current protocol appears promising in its ability to detect NAWM changes, histopathological correlates are needed to validate this approach in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%